Pengembangan Modul Mata Pelajaran Pendidikan Pancasila Dan Kewarganegaraan (PPKn) Untuk Siswa SMK - Didik Siswanto (Universitas Batanghari Jambi, 2020)
The learning process in the clasroom has been focused on teacher centered learning even though student actually also have the potential to gain knowledge independently. The implementation of learning the Pancasila and Citizenship Education subjects has so far impressed that only teachers have extensive knowledge so that lectures and notes are a way of providing material to students. Meanwhile, to get the desired competence, the learning process must be supported by adequate learning facilities. Answering this problem, teachers as facilitators in achieving student competence are required to creatively manage learning. One way is to find alternative solutions, including by developing Modules for learning. The development of this module aims to encourage students to seek their own knowledge without having to depend on the teacher. The development model chosen is based on the Borg and Gall models. The development process is carried out in five main steps, namely: (1) Conducting analysis, (2) Designing the initial product, (3) Validating and revising, (4) Small-scale field trials, and (5) Large group field trials. Based on the results of field trials, the PPKn subject modules are very well qualified, meaning that the PPKn subject modules are interesting, according to the needs and characteristics of students. Furthermore, with the results of the large group trial which concluded that by using the PPKn subject module, student scores increased, this was indicated by the value that was above the value of the minimum completeness criteria. With the existence of the PPKn subject module for vocational students, in the future students will no longer depend on the material presented by the teacher in class, but are able to obtain their knowledge independently. Furthermore, in the future learning is no longer focused on teachers but is already focused on students. Then for perfection in the future it is better if the trial use of the module is more expanded so that the results can be a reference for teachers to prepare learning teaching materials.